Facile synthesis of Al-based MOF and its applications in desiccant coated heat exchangers. (April 2022) - Ge, Lurong; Ge, Tianshu; Wang, Ruzhu
Abstract: Desiccant coated heat exchangers (DCHEs) which decouple latent load and sensible load are promising for achieving energy-efficient air-conditioning. The dehumidification performance of the DCHE is highly dependent on the desiccant properties. However, current desiccants such as silica gels, zeolites and salt-supported composite sorbents suffer from the problems of low adsorption capacity, high generation temperature or corrosion. Metal-Organic Frameworks (MOFs) with high adsorption capacity and moderate regeneration temperature are investigated for DCHE in this work. A facile method is proposed to synthesize Al-based MOFs (MIL-96 and MIL-100) with aluminum ions from the dissolution of the aluminum element. Material, coating sample and system levels experiments are conducted to evaluate the application of MOFs in the DCHE. The equilibrium water uptake of the Al-based MOFs can reach 0.35 g/g at 20 °C and 70% RH. The MOFs coating exhibited fast kinetics and excellent cycling stability after 100 adsorption-desorption cycles. An experimental setup is built up to study the dehumidification performance and the parameter influence of the MOF coated heat exchanger (MCHE). Results suggest that low inlet air velocity (<1.4 m/s) and high hot water temperature (>50 °C) help to enhance the dehumidification performance of the MCHE. Compared with the silica gel coated heat exchanger (SCHE), the MCHE displays a larger dehumidification capacity which is 2–3 times that of the SCHE under most test conditions. Moreover, the MCHE has stronger universality to different climates. This study is expected to provide a reference for the design of MOF-based dehumidification systems. Highlights: Investigation of the dehumidification performance of the MOF coated heat exchanger. Facile synthesis of Al-based MOFs and binder-free coating method. Equibirum water uptake of the MOF material at 20 °C and 70% RH was 0.35 g/g. Fast kinetics and excellent cycling stability after 100 cycles. 2–3 times the dehumidification capacity of the silica gel coated heat exchanger.